Mycobacterium branderi Infection in a Horse with Granulomatous Mesenteric Lymphadenitis. (April 2019) - Silva, F.S.; Lorenzett, M.P.; Bianchi, M.V.; Bastos, H.B.A.; Larentis, G.R.; Paul, L.G.; Snel, G.G.M.; Oliveira-Filho, J.P.; Mattos, R.C.; Sonne, L.
Summary: Although relatively uncommon in horses, infections caused by Mycobacterium spp. may affect the gastrointestinal tract. Mycobacterium branderi is a non-tuberculous Mycobacterium (NTM) that causes respiratory infections in man. Non-tuberculous mycobacteria may also affect horses; however, infection by M. branderi has not yet been reported in this species. This report describes the clinical, pathological, microbiological and molecular findings of M. branderi infection in a horse, causing granulomatous mesenteric lymphadenitis. A 17-year-old Thoroughbred stallion had a 3-month history of chronic diarrhoea, cachexia and ventral and cervical oedema. Necropsy examination revealed severe mesenteric lymphadenomegaly, together with mesenteric lymphangiectasia and diffuse small intestinal mucosal thickening. Microscopically, the mesenteric lymph node had diffuse granulomatous inflammatory infiltration, replacing most of the nodal parenchyma, with multiple acid-fast bacilli within the cytoplasm of macrophages. There was also diffuse lymphangiectasia. Fresh samples of mesenteric lymph nodes yielded no bacterial growth; however, nested polymerase chain reaction products obtained from the mesenteric lymph node samples were consistent with M. branderi . This infection should be included as a differential diagnosis in cases of chronic diarrhoea in horses, especially when granulomatous enteritis and lymphadenitis are also observed.